Levantamento de Meloidogyne spp. em áreas de cultivo de alface na região agreste do estado de Alagoas - Assunção, Mayara Castro (2016)
Lettuce (Lactuca sativa) is the most important consumed vegetable leaf in Brazil and worldwide, with an estimated planted area of approximately 30 thousand hectares/year. In the state of Alagoas, the Agreste region accounts for most of the lettuce production, including seven production areas that accounts for 90% of the vegetable consumed within the state. Among the main plant disease problems affecting lettuce production, the incidence of Meloidogyne spp. significantly affects crop yield, because most cultivars are susceptible to these nematodes. The objectives of this study were to survey lettuce production areas for the presence of Meloidogyne spp. and to identify the major nematode species and races that occur in the crop grown in the Agreste region within the state of Alagoas. Forty-two areas were sampled by collecting roots and rhizospheric soil in seven municipalities. Subsequently, lettuce roots exhibiting symptom of root-knot nematode infection were chopped and inoculated in tomato plants Santa Cruz ‘Kada’ grown in pots with sterile soil in a greenhouse. Meloidogyne species were identified based on isozyme esterase analysis. To identify races, five M. incognita populations were evaluated by the differential host test, in cotton ‘Deltapine 16’ and tobacco ‘NC 95’. The experimental design was completely randomized, with six replicates. Evaluation of nematode’s population for race identification was completed 60 days after inoculation. Only in 23 samples the multiplication of Meloidogyne spp. were observed in tomato roots. Meloidogyne incognita phenotypes I1 and I2, and M. javanica phenotype J3, were detected in 20 and in three areas, respectively. Races 2 and 4 were detected in five M. incognita populations. The presence of these nematodes species in lettuce producing areas, may result in yield losses due to their detrimental effect on the crop. Thus, the adoption of management techniques is required to keep Meloidogyne spp. populations under the damage threshold level.